The Thirties : Influences on Abstract Art in Britain. - Juda, Annely; Nakov, Andrei (London : Annely Juda Fine Art, 1998)
Arp, Hans (Jean) ; Bill, Max ; Gabo, Naum ; Hepworth, Barbara ; Kliun, Ivan ; Klucis, Gustav ; Kupka, Frantisek ; Malevich, Kasimir ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Moore, Henry ; Nicholson, Ben ; Popova, Liubov ; Rodchenko, Alexander ; Suetin, Nikolay ; Taeuber-Arp, Sophie ; Vantongerloo, Georges ; Vordemberge-Gildewart, Friedrich
geboortedatum, tent., bibliog. per kunstenaar
Engels
The Thirties : Influences on Abstract Art in Britain, Annely Juda Fine Art, London, 2 July - 19 September 1998
boek
Keywords: Groot-Brittannië